Exploration and identification of six novel ferroptosis-related hub genes as potential gene signatures for peripheral nerve injury - Zhang, Yifei; Chen, Chun; Li, Dawei; Chen, Penghui; Hang, Lei; Yang, Jun; Xie, Jin (Frontiers in Genetics, 2023)
Specific biomarkers of ferroptosis after peripheral nerve injury (PNI) are still under debate. In this study, 52 differentially expressed ferroptosis-related genes (DE-FRGs) were retrieved from publicly accessible sequencing data of intact and injured samples of rats with sciatic nerve crush injury. Functional enrichment analyses revealed that adipogenesis, mitochondrial gene sets, and pathways of MAPK, p53, and CD28 family were predominantly engaged in ferroptosis after PNI. Next, Cdkn1a, Cdh1, Hif1a, Hmox1, Nfe2l2, and Tgfb1 were investigated as new ferroptosis-associated hub genes after PNI. Subsequently, clustering correlation heatmap shows six hub genes are linked to mitochondria. The immunofluorescence assay at 0, 1, 4, 7, and 14 d indicated the temporal expression patterns of Tgfb1, Hmox1, and Hif1a after PNI were consistent with ferroptosis validated by PI and ROS staining, while Cdh1, Cdkn1a, and Nfe2l2 were the opposite. In summary, this study identified six hub genes as possible ferroptosis-related biomarkers for PNI, which may offer therapeutic targets for peripheral nerve regeneration and provide a therapeutic window for ferroptosis.